Avaliação de políticas públicas: o caso do Programa Nacional de Formação em Administração pública (PNAP) no Brasil - Savi, Claudia Aparecida (2020)
The National Program of Formation in Public Administration (PNAP) was implemented in 2009 as an initiative of the Open University System of Brazil (UAB) and the Coordination for the Improvement of Higher Education Personnel (CAPES) in partnership with many Public Institutions of Higher Education, as a strategy to strengthen Public Administration, especially on the local scope. The PNAP was conceived and structured in an innovative way, decentralizing the opportunities in free and solid higher education training for public managers, enabling them to intervene on social, political and economic reality, contributing with managerial advance on the activities performed by the Brazilian State within the federal, state and municipal levels. In total 81 IPES from all regions of the country joined the program announcements and are or have been in charge of its implementation. The present research has the main purpose of evaluating the National Program of Formation in Public Administration, from 2009 to 2019, from the formulation context, its content, its institutional trajectory, the temporal and territorial spectrum and the local agents’ actions in promoting endogenous regional development as a mechanism for training students and public managers. The specific objectives are: discuss the models of social policy evaluation and their relation to regional and local endogenous development; characterize the political, socioeconomic and institutional context of PNAP from 2009 to 2019; and discuss the PNAP process of implementation as an action of endogenous regional development local agents. In order to meet the goals of the current study, the qualitative research was chosen through the PNAP case study by conducting bibliographic, documentary and field research, the latest done through an online questionnaire to the PNAP course coordinators and the classroom poles coordinators from the UAB System, where the PNAP courses are offered, across all the Brazilian territory. The main results show that the program has fulfilled its objectives regarding to the public management formation, strengthening the public management in the country, especially on local basis. It also emphasizes the local agents’ strength as protagonists of regional endogenous development who contribute to the viability of changes in the surrounding, providing opportunities and expanding training for the local population, increasing the public agents’ action, or for those interested in public management and, thus, empowering the place. The social gains are the training carried out and the potential effects on the place from this greater human source development. However, operationally, the program still has challenges to be overcome, such as: high evasion, not being an institutionalized practice in the IPES, regular training on distance education practices for tutors and annual discontinuity in vacancies offer due to the federal government budget restrictions.